Philanthrocapitalism as wealth management strategy: Philanthropy, inheritance and succession planning among the global elite. Issue 2 (March 2021) - Sklair, Jessica; Glucksberg, Luna
In the resurgence of interest in inheritance flows following the publication of Piketty's work, little attention has been paid to the affective practices that ensure the success of inheritance processes as wealth moves down generations of dynastic families. This article explores these practices, drawing on research among wealth managers, philanthropy advisors, family offices and their clients, to show how philanthropy is promoted by advisors to the wealthy as a tool to support inheritance and family business succession planning. In this process, advisors draw on the philanthropic imagination to style wealthy families as custodians of both private capital and the common good, thus mirroring the narratives used by philanthrocapitalists to legitimise their wealth in the public sphere. Here, however, the discourse of philanthrocapitalism is turned inwards to the private realm of the family, to persuade younger generations to rally around the collective project of the custodianship of wealth. By bringing together research on philanthropy and inheritance, this article contributes to the growing sociological literature on elites and the global inequalities driven by their accumulation of wealth. It shows how wealth accumulation is increasingly dependent not only on the mechanics of financial markets and inheritance flows, but also on affective wealth management strategies framed around ethical notions of kinship and social responsibility.